2021
DOI: 10.31235/osf.io/t8xar
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Outbreak of Selective Attribution: Partisanship and Blame in the COVID-19 Pandemic

Abstract: Crises and disasters give voters an opportunity to observe the incumbent's response and reward or punish them for successes and failures. Yet even when voters agree on the facts, they tend to attribute responsibility in a group-serving manner, disproportionately crediting their party for positive developments and blaming opponents for negative developments. Using original time series data, we show that partisan disagreement over U.S. President Donald Trump's responsibility for the COVID-19 pandemic quickly eme… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…A different line of research focuses on the role of political preferences. Although some studies have reported that stronger conservatism is linked to motivated beliefs about political topics (Braman & Nelson, 2007; Caddick & Feist, 2021; Graham & Singh, 2023; Jost et al, 2003; Miller et al, 2016; Osmundsen et al, 2021; Saunders, 2017), others have failed to find such an effect (Ditto et al, 2019; Eichmeier & Stenhouse, 2019; Guay & Johnston, 2022; Kahan, 2012).…”
Section: Influence Of Individual Differences On Motivated Cognitionmentioning
confidence: 99%
“…A different line of research focuses on the role of political preferences. Although some studies have reported that stronger conservatism is linked to motivated beliefs about political topics (Braman & Nelson, 2007; Caddick & Feist, 2021; Graham & Singh, 2023; Jost et al, 2003; Miller et al, 2016; Osmundsen et al, 2021; Saunders, 2017), others have failed to find such an effect (Ditto et al, 2019; Eichmeier & Stenhouse, 2019; Guay & Johnston, 2022; Kahan, 2012).…”
Section: Influence Of Individual Differences On Motivated Cognitionmentioning
confidence: 99%
“…Yet, there exist many sources of error that lead to misattributions. These include overweighing recent events (e.g., focusing on a recent transgression rather than a history of transgressions) (Huber et al., 2012), making attributions based on perceptions of the competence of relevant actors that may or may not be accurate (Graham & Singh, 2023), making attributions based on random events that alter one's mood (e.g., Achen & Bartels, 2016; Busby et al., 2015; Healy et al., 2010; cf. Fowler & Hall, 2018), only blaming those from the out‐party (Malhotra & Kuo, 2008), and being vulnerable to blame‐shifting rhetoric (Schlipphak et al., 2022).…”
Section: Social Mobilizationmentioning
confidence: 99%
“…Partisans are much more likely to follow suggestions and absorb information when it is presented to them by leaders in their own party, as compared to non-partisan figures and especially figures from the opposing party. This partisan cuing effect extends to a variety of topics, including vaccination (Weisel 2021), mask-wearing (Milosh et al 2020), and COVID-19 blame attribution (Graham and Singh 2021). This suggests that Republicans, whose party leaders and media outlets engaged in anti-Asian cuing behavior, should be more likely to respond with consumer discrimination against Chinese and Asian restaurants, leading to Hy- Finally, we propose a potential mechanism for spillovers to non-Chinese Asian restaurants (such as "Tiger Belly Noodle Bar") whose names are ethnically ambiguous but could potentially be classified as Chinese.…”
Section: Introductionmentioning
confidence: 99%